Precision livestock farming: An overview (Indian Journal of Animal Production and Management, 2017)
Global human population is increasing gradually and still hungry hence more food is required  to satisfy the mankind. The demand of animal products is increasing as most people can afford foods of  animal origin. We are enforced to achieve high-quality, sustainable and safe food production that can meet  the demand of the people. At present, we need a farming system that is farmer friendly by providing profit  to the farmer, people friendly by safe and quality products to the people, planet friendly by causing least  harm to the environment and also animal friendly to ensure animal welfare. Precision livestock farming  provides facilities for such farming system. It uses sensors and soft wares for automatic and continuous  monitoring of each and every activities of animal, which are used to optimize contribution of every animal.  In future, this farming approach may be adopted by most of the farmers.
Keywords: Animal products; Automatic monitoring; Precision; Sustainable